Unemployment And Economic Development In Nigeria (1980-2017) - Ojima, Davis (Advances in Social Sciences Research Journal, 2019)
Unemployment is a global phenomenon which has attracted the attention of developed and developing nations because of its attendant consequences. Given the incidence of unemployment in the country and its attendant consequences this study investigates the empirical relationship between unemployment and economic development in Nigeria. Using the ordinary least technique and time series data from 1980-2017, the study explored the relationship between unemployment and economic development in Nigeria. The result shows that unemployment has negative effect on economic development of Nigeria. This implies that an inverse relationship exist between unemployment and economic development in Nigeria. In the light of the findings, the study recommended that the government should create employment opportunities in order to reduce drastically our unemployment rate, fiscal policy and monetary policy that can induce job creation should be adopted. Skill acquisition and on the job training programmes should be highly encouraged so as to achieve sustainable economic growth and development in Nigeria.